Microbial succinate promotes the response to metformin by upregulating secretory immunoglobulin a in intestinal immunity - Ying Zhang; Aiting Wang; Wei Zhao; Jia’an Qin; Yu Zhang; Bing Liu; Chengcheng Yao; Jianglan Long; Mingxia Yuan; Dan Yan (Gut Microbes)
Metformin is the first-line pharmacotherapy for type 2 diabetes mellitus; however, many patients respond poorly to this drug in clinical practice. The potential involvement of microbiota-mediated intestinal immunity and related signals in metformin responsiveness has not been previously investigated. In this study, we successfully constructed a humanized mouse model by fecal transplantation of the gut microbiota from clinical metformin-treated – responders and non-responders, and reproduced the difference in clinical phenotypes of responsiveness to metformin. The abundance of Bacteroides thetaiotaomicron, considered a representative differential bacterium of metformin responsiveness, and the level of secretory immunoglobulin A (SIgA) in intestinal immunity increased significantly in responder recipient mice following metformin treatment. In contrast, no significant alterations in B. thetaiotaomicron and SIgA were observed in non-responder recipient mice. The study of IgA˗/˗ mice confirmed that downregulated expression or deficiency of SIgA resulted in non-response to metformin, meaning that metformin was unable to improve dysfunctional glucose metabolism and reduce intestinal and adipose tissue inflammation, ultimately leading to systemic insulin resistance. Furthermore, supplementation with succinate, a microbial product of B. thetaiotaomicron, potentially reversed the non-response to metformin by inducing the production of SIgA. In conclusion, we demonstrated that upregulated SIgA, which could be regulated by succinate, was functionally involved in metformin response through its influence on immune cell-mediated inflammation and insulin resistance. Conversely, an inability to regulate SIgA may result in a lack of response to metformin.